Technology and society : a world history - Ede, Andrew (Cambridge : Cambridge University Press, 2019)
"Technology and Society Technology and Society: A World History explores the creative power of humanity from the age of stone tools to the digital revolution. It introduces technology as a series of systems that allowed us to solve real-world problems and create a global civilization. The history of technology is also the history of the intellectual and cultural place of our tools and devices. With a broad view of technology, we can see that some of the most powerful technologies such as education and government produce no physical object but have allowed us to coordinate our inventive skills and pass knowledge through the ages. Yet although all human communities depend on technology, there are unexpected consequences from the use of technology which, as Ede shows, form a crucial part of this rich story"--
Thinking about technology -- Techonology and our ancient ancestors -- Origins of civilizations -- The Eastern age -- The Mediterranean world to the Islamic renaissance -- The European agrarian revolution and the proto-industrial revolution -- The industrial revolution and the rise of European power -- The Atlantic era I -- Domestic technology : bringing new technology to the people -- The second industrial revolution and globalization -- The digital age -- Conclusion : Technological challenges.
Includes bibliographical references and index.
Keywords: Technology -- Social aspects